A European Union corporate due diligence act for whom? Considerations about the impact of a European Union due diligence act on artisanal and small-scale cobalt miners in the Democratic Republic of Congo. (March 2023) - Elbel, Johanna; Bose O'Reilly, Stephan; Hrzic, Rok
Abstract: Background: Cobalt is a key mineral for the European Unions (EU) growing electrical vehicle market. It is widely held by international NGOs and researchers that the extraction of this mineral is associated with human rights violations. This study investigates the expected consequences of an EU Due Diligence Act on the health of artisanal and small-scale cobalt miners in the Democratic Republic of Congo (DRC) based on the perspectives of stakeholders. Methods: Semi-structured open-ended qualitative interviews (n = 7) with researchers, non-governmental workers, representatives of a trade organisation and policymakers were conducted between February 2021 and April 2021. The Capability Approach focusing on agency and participation of the DRC's mining population was operationalised in the coding scheme. The software NVivo was used for coding and analysing the data. Results: An EU Due Diligence Act was welcomed by the interviewed stakeholders. They expect the act to positively impact supranational human rights and environment protection standards in non-European regions. The impact on the health of miners will occur indirectly through monitoring and formalisation efforts and is expected to be positive when accounting for complex contextual factors. Conclusions: Artisanal and small-scale cobalt miners should be included in international discussions about due diligence and their needs considered in the final version of the law to ensure it positively impacts health outcomes. Mandatory proactive engagement of businesses in the artisanal and small-scale cobalt mining sector with a focus on long-term approaches, partnerships, and collaborative efforts is recommended. Highlights: An EU Due Diligence Act is unlikely to directly improve artisanal and small-scale cobalt miners' health in the DRC. Context-dependent reforms may sustainably improve working conditions for artisanal and small-scale cobalt miners in the DRC. Proactive engagement by political actors to empower the artisanal and small-scale cobalt mining sector is essential.